Penelitian daam Bahasa Asing - Saparripin Idris (Hikmah, 2018)
The title of this writing is; “The Research in Teaching Foreign Language”. The research was aimed to research teaching learning foreign language and how to support the teachers and students in teaching learning process. Because the need for knowledge of understanding of teaching learning foreign language. It is the most important thing to reach successfully. It can begin with a focus on the scientific research, such as; the typology research, the concept fact and construction, language teaching and action research. These steps consist of steps micro and macro as part.